A study of awareness of cyber scams and cybersecurity among university students in Malaysia - Bong, Xu Lin (2023)
The number of Malaysians using social media has grown. The availability of the infinite social network has been linked to a rise in the occurrence of cybercrimes in Malaysia. Based on the cases that have taken place, most cases are due to lack of awareness of cyber scams and cybersecurity. Therefore, this study aimed at measuring the awareness level of different cyber scams and discovering awareness of cybersecurity among Malaysian university students. In this study, quantitative online surveys were used during the data collection process. A total of 50 respondents have been involved in this survey. As a result, it showed that respondents had the highest level of awareness of merchant fraud. For awareness in cybersecurity, university students were more conscious of their privacy. A cybersecurity awareness program can be conducted as a suggestion in any tertiary institutions. Hopefully this study will reduce the number of cases of cyber scams and at the same time, strengthen the awareness of the major concern group, university students in Malaysia.